Parámetros productivos de pollos guaricos (Gen Nana) en pastoreo suplementados con harina de de hojas de yuca (Manihot esculenta Crantz) - Pincay Jiménez, Roberto Carlos (2017)
In the "La María" experimental farm, in the poultry poultry program, Faculty of Animal Sciences, Quevedo State Technical University (UTEQ), located at km 7 of the Quevedo- El Empalme road, Mocache (Gen Nana) grazing supplemented with cassava leaf meal (Manihot esculenta Crantz), with a duration of thirteen weeks, with the objective of evaluating the effects of the use of the leaves of manihot (Manihot esculenta Crantz) (Hhy) included in diets for guarico chickens (Gen Nana) in grazing. The variables to be investigated were; (g), weight gain (g), feed conversion, yield (%) and economic analysis of the treatments. Four treatments and six replications were used with a total of 96 birds (4 birds / replicate). The treatments were T1 = control (commercial balance), T2 = (commercial balance + 6% Hhy), T3 = (commercial balance + 9% Hhy), T4 = (commercial balance + 12% Hhy). There were significant differences (P <0.05) for total food consumption, treatments containing inclusions (6, 9 and 12%) showed no difference between them as compared to the control treatment (T1), the highest consumption was presented by treatment control with (8258.33g) and the lowest, T3 treatment (9% Hhy) (7597.0 g) with a probability (0.030). In the variable weight gain, significant differences (P <0.05) were observed among the evaluated treatments, T1 Control achieved the highest total weight gain (2462.50 g) and the lowest gain was T4 (2153.0g) with a probability (0.024). In the feed conversion, T1 obtained the best results (3.63) than the other treatments. The animals that consumed the 9% inclusion of Hhy in the diets presented higher profitability.